(untitled) (IAHS Medical Journal, 2023)
Background: Patients having elective abdominal surgery under general anesthesia often have Postoperative Nausea and Vomiting (PONV). In this study the main goal is to evaluate the outcome of Aprepitant/Dexamethasone (A/D) combination vs Mirtazapine/Dexamethasone (M/D) combination vs Dexamethasone (D) alone for prevention of PONV in individuals after abdominal surgery. Materials and methods: This cross sectional study was carried out at tertiary medical hospital from January 2021 to January 2022. Where a total of 150 patients scheduled for abdominal surgery were randomly allocated to receive 8 mg dexamethasone Intravenous Infusion (IVI) only in the D group or in addition to 80 mg aprepitant capsule in the A/D group or in addition to 30 mg mirtazapine tablet in the M/D group. In each 50 patients divided to each group. Assessment of PONV was carried out at 0–2 h (Early) and 2–24 h (Late). The primary outcome was the complete response 0-24 h after surgery. Collective PONV, postoperative pain, side effects and patient satisfaction score were considered as secondary outcomes. Results: Majority of the study populations belonging to 41-50 years age group (65%) and 60% of them were male. In concordance to that, the intraoperative variables of duration of surgery and mean given intravascular fluid volume were comparable between groups. In the early postoperative period (0–2 h), there was a statistically significant difference between the A/D group and the D group in the number of vomiting episodes with comparable efficacy between the A/D and M/D groups. There were no statistically significant differences between the studied groups regarding nausea episodes, collective PONV, rescue antiemetic usage, and the number of patients exhibiting a complete response. Pain score at (0–2 h) was significantly higher in the D group in comparison to the A/D and M/D groups with comparable efficacy between the A/D and M/D groups (p < 0.001). The rescue analgesic doses were significantly higher in the D group compared to the A/D and M/D groups with statistically significant differences between the A/D and M/D groups (p < 0.001). in addition, more patients in the A/D and M/D groups were satisfied with the PONV prevention protocol compared to the D group. Conclusion: The combination of aprepitant and dexamethasone, as well as mirtazapine and dexamethasone, has been proven to be more effective than dexamethasone alone in reducing postoperative nausea and vomiting in critically ill patients following abdominal surgery. IAHS Medical Journal Vol 5(2), Dec 2022; 29-33